THE ANALYSIS OF METAPHOR IN WESTLIFEâS SONG LYRICS - NDRAHA, LIES DIAN MARSA (Institut Pendidikan Tapanuli Selatan, 2018)
Metaphors are usually used by Westlife in their lyrics to express what they mean in order to transfer the message they want to send to the listeners in expressing their feeling. But most of people who is interested to listen and sing the Westlifeâs song lyrics do not understand the metaphor that exist in Westlifeâs song lyrics. Therefore, the focus of the research is how is the metaphor used in Westlifeâs song lyrics? This research was designed in qualitative research. The technique of descriptive analysis was applied to analyze data by reading the data and identify the types of metaphor used in the lyric of songs based on Goatlyâs book. Based on research finding, the researcher found 19 of metaphor used in the Westlifeâs song lyrics. And each metaphors were found in the lyric of Westlifeâs songs try to tell us about human social life which contained about love, sadness, happiness, spirit and others. In line with conclusion, the researcher suggests that readers could develops their knowledge of metaphors. This result hopefully would help English teacher to use metaphor in teaching process, and use the metaphor in the classroom can be an effective way of expanding studentsâ vocabulary.